Educational, Linguistic, and Media Discourses - Kriaučiūnienė, Roma (Cambridge Scholars Publisher, 2020)
This book presents a collection of research papers from both experienced and emerging scholars, some of whom presented their work at the international conference 'Language Teaching and Learning in the 21st Century: Linguistic, Educational and Intercultural Aspects' held in June 2018 and organised by the Institute of Foreign Languages of the Faculty of Philology of Vilnius University, the FIPLV Nordic-Baltic Region, and the Language Teachers' Association of Lithuania. The book consists of three parts, the first being devoted to language teaching and teacher education. The second section explore.